Cultivation and Functional Properties Characterization of “Cendawan Busut” (Termitomyces sp.) Locally Isolated in Negeri Sembilan - Srivani Sellathoroe (Universiti Sains Islam Malaysia, 2024)
Matric: 3192553 (FST)